The three faces of Greek and Aristotelian rhetoric (2017)
The need for the persuasion is often informed by a dire or grave situation which one needs to wriggle out from. Persuasion may also be necessitated by a person’s disposition to a subject, development, or topic in view. The art of persuasion through speech is what scholars, ancient and modern, call rhetoric or oratory. The Greek traditional theorists, who invented rhetoric, divided the art into three types: the judicial (dicanic or forensic), the deliberative (symbouleutic) and the demonstrative (epideictic). Broadly, Greek rhetoric also has a tripartite part: invention, arrangement and style. Similarly, by Aristotelian theory, rhetoric is the art of persuasion which functions by three means: by appeal to people’s reason (logos); by the appeal to their emotions (pathos) and by the appeal of the speaker’s personality or character (ethos). What exactly did the Greeks and, indeed, Aristotle mean by these terms and their functions? This paper, while highlighting the general conception of the Greek rhetoric and its three-way nature, surveys the Aristotelian tripartite division and functionality of rhetoric through a simple method of content analysis of selected ancient and modern texts. It submits that a rhetor (rhetorician/orator) is not firm in his trade if he does not artfully possess and execute the Aristotelian three modes of persuasion in contexts of necessity or grave situations